2018
DOI: 10.1002/jclp.22614
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems among clinical psychologists: Stigma and its impact on disclosure and help‐seeking

Abstract: Personal experiences of mental health problems among clinical psychologists may be fairly common. Stigma, concerns about negative consequences of disclosure and shame as barriers to disclosure and help-seeking merit further consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
8
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(144 citation statements)
references
References 42 publications
12
114
8
10
Order By: Relevance
“…Disclosure to employers rarely occurred. Participants were also unlikely to seek specialist professional assistance, only 3.8% of those who had experienced a mental health problem had done so …”
mentioning
confidence: 99%
“…Disclosure to employers rarely occurred. Participants were also unlikely to seek specialist professional assistance, only 3.8% of those who had experienced a mental health problem had done so …”
mentioning
confidence: 99%
“…In a recent study of clinical psychologists in the United Kingdom, Tay, Alcock, and Scior (2018) found similar figures to Gilroy and colleagues (2002). An invitation to complete the survey was emailed to the 3,600 qualified clinical psychologists who were on the mailing list of the British Psychological Society's Division of Clinical Psychology (DCP).…”
Section: Psychologists' Own Mental Illnesssupporting
confidence: 71%
“…In addition, mental health professionals who have their own mental illness have reported experiences of stigmatization from colleagues (Knaak et al, 2017;Zeruvabel & Wright, 2012;Cain, 2000). This is considering that studies have estimated 60-70 percent of psychologists have experienced some mental illness -in most cases mild to moderate depression -in their lifetime (Pope & Tabachnick, 1994;Gilroy, Murra, & Carroll, 2002;Tay, Alcock, & Scior, 2018). That said, far fewer psychologists (about 10 percent or less) reported having what might be categorized as severe mental illness, including severe depression, psychosis, bipolar disorder, more than passive suicidal ideation, or any mental illness that resulted in hospitalization (Pope & Tabachnick, 1994;Gilroy, Murra, & Carroll, 2002;Tay, Alcock, & Scior, 2018).…”
Section: Chapter 1 General Introduction/overviewmentioning
confidence: 99%
“…Mental health problems are prevalent among psychologists and other therapists working in psychiatric health care services. In a recent survey of 678 clinical psychologists in the UK (Tay et al, 2018), 63% reported having experienced self-defined mental health problems at some point in their lives, particularly anxiety and depression. This compares with a 43% lifetime prevalence of mental health problems in the general adult population in the UK (Mental Health Foundation, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors are high emotional demands and stresses inherent in working with patients in this field, an isolating work situation with limited contact with colleagues and confidentiality obligations, a 'professional blind spot' with regard to own mental health problems due to being trained to attend to others' problems, and those with lived experience may be more likely to be attracted to this line of work . In addition, stigma, shame and concerns about negative consequences for career may prevent disclosure and help-seeking (Tay et al, 2018), which may further exacerbate mental health problems.…”
Section: Introductionmentioning
confidence: 99%